1998
DOI: 10.1111/j.1469-7793.1998.895bm.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory modulation of carotid and aortic body reflex left ventricular inotropic responses in the cat

Abstract: Several studies have demonstrated that the cardiac chronotropic responses to selective stimulation of the carotid body chemoreceptors are respiratory modulated. The reflex bradycardia of vagal origin is greater when the excitatory stimuli are delivered in the expiratory phase of the respiratory cycle than when delivered in the inspiratory phase (Haymet & McCloskey, 1975; see also Spyer, 1990). This is accounted for by the excitability of the cardiac vagal preganglionic motoneurones near the nucleus ambiguus va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…2014; Tubek et al . 2016), the CO response to hypoxia in bCBR patients most likely reflects undisturbed functionality of aortic bodies to increase HR and contractility (De Burgh Daly & Jones, 1998) and is in line with the maintained (in comparison to pre‐procedural values) HR slope. We believe that preservation of HR reactiveness to hypoxia cannot be attributed to the activation of pulmonary stretch receptors as ventilatory response to hypoxia in bCBR patients is absent.…”
Section: Discussionmentioning
confidence: 82%
“…2014; Tubek et al . 2016), the CO response to hypoxia in bCBR patients most likely reflects undisturbed functionality of aortic bodies to increase HR and contractility (De Burgh Daly & Jones, 1998) and is in line with the maintained (in comparison to pre‐procedural values) HR slope. We believe that preservation of HR reactiveness to hypoxia cannot be attributed to the activation of pulmonary stretch receptors as ventilatory response to hypoxia in bCBR patients is absent.…”
Section: Discussionmentioning
confidence: 82%
“…1997; Brophy et al . 1999), but their ventilatory significance is dubious because no respiratory response could be demonstrated when the aortic bodies were selectively stimulated and no additional effect on hypoxic ventilatory response was observed after aortic nerve transection in chemodenervated rats (De Daly & Jones, 1998; Martin‐Body et al . 1986).…”
Section: Discussionmentioning
confidence: 99%
“…There is also some inconsistency in the relative roles of the CB and the ABs in modulating ventilation during hypoxia. [7][8][9][10][11][12] Previous studies have shown that stimulation of the ABs using sodium cyanide infused into the aortic arch as well as systemic hypoxia caused hyperventilation even post CB denervation in the dog, 7 indicating that the ABs do play a role in the ventilatory response to hypoxia.…”
Section: Respiratory Regulation By Absmentioning
confidence: 99%
“…5,6 Gaseous or chemical stimulation of ABs produces a mild increase in ventilation compared with activation of the CBs in anesthetized animals. 7–12…”
mentioning
confidence: 99%
See 1 more Smart Citation